2017
DOI: 10.11604/pamj.2017.26.208.12148
|View full text |Cite
|
Sign up to set email alerts
|

Césarienne à Lubumbashi, République Démocratique du Congo II: facteurs de risque de mortalité maternelle et périnatale

Abstract: IntroductionL’objectif était d’analyser les facteurs de risque de mortalité maternelle et périnatale de la césarienne à Lubumbashi, République Démocratique du Congo (RDC).MéthodesÉtude multicentrique de 3643 césariennes réalisées entre le 1er janvier 2009 et le 31 décembre 2013 sur un total de 34199 accouchements dans cinq formations hospitalières de référence à Lubumbashi (RDC). Les données sociodémographiques, les indications, l’environnement obstétrical et la morbi-mortalité maternelles et périnatales ont é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
3
3
2
2
Order By: Relevance
“…Nonetheless, wealth quintile-specific analysis further indicated that the poorest had the highest odds (OR,4.4) of cesarean-related neonatal deaths even though they had the lowest cesarean delivery rates. These findings partly concur with previous health facility-based studies across many low-and middle-income settings that suggest that cesarean delivery (CD), both emergency and planned, has had net poor perinatal and neonatal outcomes [5,[22][23][24][25][26][27][28] This study is perhaps the first of its kind to examine the influence of socioeconomic factors on cesarean delivery and neonatal survival outcome resulting from C-section at national levels in Kenya and Tanzania. C-section as an increasingly preferred mode of birth does not guarantee better neonatal outcomes in East Africa.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nonetheless, wealth quintile-specific analysis further indicated that the poorest had the highest odds (OR,4.4) of cesarean-related neonatal deaths even though they had the lowest cesarean delivery rates. These findings partly concur with previous health facility-based studies across many low-and middle-income settings that suggest that cesarean delivery (CD), both emergency and planned, has had net poor perinatal and neonatal outcomes [5,[22][23][24][25][26][27][28] This study is perhaps the first of its kind to examine the influence of socioeconomic factors on cesarean delivery and neonatal survival outcome resulting from C-section at national levels in Kenya and Tanzania. C-section as an increasingly preferred mode of birth does not guarantee better neonatal outcomes in East Africa.…”
Section: Discussionsupporting
confidence: 88%
“…Elective CD has been associated with sepsis and respiratory problems, which are major causes of neonatal deaths globally [19]. While cesarean delivery has prevented many adverse pregnancy outcomes, the quality and conditions under which some procedures (both elective and emergency) are executed in many low-resourced settings have also resulted in many morbidities [20,21] and preventable mortalities [5,[22][23][24][25][26][27][28]. The trade-offs between morbidities and benefits are generally unclear but also costly for weak health-care systems [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of included articles by country was as follows:, Algeria [60], Benin [78], Burkina Faso [122,143], Cameroon [99,133], Democratic Republic of Congo [55,82], Egypt [105], Eritrea [102], Ethiopia [57,62,71,72,74,86,130,131], Ghana [49,52,53,58,69,141], Guinea-Bissau [76], Kenya [63,91,110,123,142,145], Madagascar [79], Malawi [80,83,100,126,140], Morocco [44], Mozambique [59], Nigeria [42,43,45,47,48,54,56,65,67,89,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Définition des variables: pour la parité, nous avons défini comme pauci-pare (parité 1 à 2), multipare (parité 3 à 4) et grande multipare (parité >4) [ 22 ]. Le niveau socio-économique était classé comme bas (absence de salaire ou de source de revenus clairement définie ou ne disposant ni de téléphone ni de trousse d´accouchement), moyen (avec ou sans salaire mais disposant d´un téléphone fonctionnel et d´une trousse d´accouchement) et élevé (salaire disponible avec avantages liés à la fonction, disposant d´un téléphone fonctionnel et d´une trousse d´accouchement) [ 23 ].…”
Section: Méthodesunclassified
“…Le niveau socio-économique était classé comme bas (absence de salaire ou de source de revenus clairement définie ou ne disposant ni de téléphone ni de trousse d´accouchement), moyen (avec ou sans salaire mais disposant d´un téléphone fonctionnel et d´une trousse d´accouchement) et élevé (salaire disponible avec avantages liés à la fonction, disposant d´un téléphone fonctionnel et d´une trousse d´accouchement) [ 23 ]. Le statut marital était classé comme marié (une femme qui vit en union) et célibataire (celle qui vit seule) [ 22 ]. Le niveau d´études était défini comme primaire (études primaires avec ou sans certificat), secondaire (études secondaires ou diplôme de fin d´études secondaires) et supérieur (études universitaires avec ou sans diplôme) [ 16 , 23 ].…”
Section: Méthodesunclassified